Clinical Significance of Nadir Hemoglobin in Predicting Neurologic Outcome in Infants With Abused Head Trauma - Lee, En-Pei; Zhao, Lu-Lu; Hsia, Shao-Hsuan; Lee, Jung; Chan, Oi-Wa; Lin, Chia-Ying; Su, Ya-Ting; Lin, Jainn-Jim; Wu, Han-Ping (Frontiers in Pediatrics, 2020)
Traumatic brain injury (TBI) is a leading cause of pediatric morbidity and mortality and is categorized as abusive head trauma (AHT) and accidental head injury. A retrospective chart review of 124 children aged <1 year diagnosed with TBI were analyzed. Outcomes were evaluated at discharge and 6 months later by using the Pediatric Cerebral Performance Category (PCPC) Scale. The receiver operating characteristic (ROC) curve was applied to determine the cutoff values for hemoglobin (HB) levels. In the study, 50 infants (40.3%) achieved a favorable neurologic outcome (PCPC ≦ 2) and 74 (59.7%) had poor neurologic outcomes (PCPC ≧ 3). Infants with poor neurologic outcomes had lower HB on admission and nadir HB (p < 0.05). Based on multivariate logistic regression analysis, the nadir HB was a predictor of poor neurologic outcomes at discharge and 6 months later in both AHT and accidental head injury. Nadir HB had the largest area under the ROC curve for predicting poor neurologic outcomes. We determined the appropriate cutoff value of nadir HB as 9.35 g/dl for predicting neurologic outcomes in infants with TBI. Furthermore, the cutoff value of nadir HB in predicting poor neurologic outcomes in infants caused by AHT and accidental head injury were taken as 9.36 and 8.75 g/dl, respectively.